Behavior Paying Premium to the Independent Participants in Healthcare Social Insurance Administration Office - Tarigan, Sylva Flora; Dondo, Marisa Lestary (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Premiums non-compliance leads to the Healthcare Social Insurance Administration Office (henceforth, will be referred to as BPJS Kesehatan) budget deficit, resulting in an accumulation of debt claims in various health facilities and an impact on the quality and quantity of health services in health facilities. As of March 2019, 38% of independent National Health Insurance (JKN) participants in Gorontalo City were not compliant to pay dues. This study objective to assess the relationship between willingness to pay with compliance behavior to pay premiums for BPJS Kesehatan independent participants. This study uses a cross-sectional study design. The population was 8,594 people who were independent BPJS Kesehatan participants with a sample of 95 people using accidental sampling techniques. Data were collected through interviews using a questionnaire, data analysis using Chi-Square test. The results showed that the distribution of the level of compliance paying BPJS premiums independently was still 64.2%. Distribution of the willingness to pay by 85%. There is a significant relationship between Willingness To Pay (WTP) with compliance paying dues with p = 0.031. There is a relationship between WTP with compliance to pay the premiums of BPJS Kesehatan independent participants in the inpatient installation at RSUD Prof. Dr. H. Aloei Saboe in Gorontalo City.